Education and pneumonia mortality: a trend analysis of its inequalities in Colombian adults. Issue 1 (16th November 2020) - Alvis-Zakzuk, Nelson J.; Arroyave, Ivan; Castañeda-Orjuela, Carlos; De La Hoz-Restrepo, Fernando; Alvis-Guzman, Nelson
Abstract : Objective: To explore the existence and trends of social inequalities related to pneumonia mortality in Colombian adults using educational level as a proxy of socioeconomic status. Methods: We obtained individual and anonymised registries from death certificates due to pneumonia for 1998–2015. Educational level data were gathered from microdata of the Colombian Demography Health Surveys. Rate ratios (RR) were estimated by using Poisson regression models, comparing mortality of educational groups with mortality in the highest education group. Relative index of inequality (RII) was measured to assess changes in disparities, regressing mortality on the midpoint of the cumulative distribution of education, thereby considering the size of each educational group. Results: For adults 25+ years, the risk of dying was significantly higher among lower educated. The RRs depict increased risks of dying comparing lower and highest education level, and this tendency was stronger in woman than in men (RR for primary education=2.34 (95% CI 2.32 to 2.36), RR for secondary education=1.77 (95% CI 1.75 to 1.78) versus RR for primary education=1.83 (95% CI 1.81 to 1.85), RR for secondary education=1.51 (95% CI 1.50 to 1.53)). According to age groups, young adults (25–44 years) showed the largest inequality in terms of educational level; RRs for pneumonia mortality regarding the tertiary educated groups show increased mortality in the lower and secondary educated, and these differences decreased with ages. RII in pneumonia mortality among adult men was 2.01 (95% CI 2.00 to 2.03) and in women 2.46 (95% CI 2.43 to 2.48). The RII was greatest at young ages, for both sexes. Time trends showed steadily significant increases for RII in both men and women (estimated annual percentage change (EAPC)men=3.8; EAPCwomen=2.6). Conclusion: A significant increase on the educational inequalities in mortality due to pneumonia during all period was found among men and women. Efforts to reduce pneumonia mortality in adults improving population health by raising education levels should be strengthened with policies that assure widespread access to economic and social opportunities.